2021
DOI: 10.1093/nutrit/nuab059
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids as anti-inflammatory agents in overweight and obesity: a systematic review and meta-analysis

Abstract: Context Short-chain fatty acids (SCFAs) derived from microbial fermentation of prebiotic soluble fibers are noted for their anti-inflammatory benefits against obese systemic inflammation. Objective A systematic review and meta-analysis were undertaken to investigate the effect of SCFAs and prebiotic interventions on systemic inflammation in obesity. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 89 publications
1
12
0
1
Order By: Relevance
“…24 Studies have indicated that various insoluble dietary fibers can be fermented by specific intestinal bacteria, or they enhance the SCFA-producing bacteria to promote the production of SCFAs, which is contributed to its anti-obesity effect. 28 In line with those reports, the administration of CL-IDFs or CL-TDFs significantly enriched the family of Lachnospiraceae and could promote SCFA production, suggesting that the anti-obesity effect was correlated with the production of SCFAs. The SCFA concentration suggests that the anti-obesity effect was correlated with the production of SCFAs.…”
Section: Effect Of the Cl-idf And Cl-tdf On Gut Microbiota And Scfas ...supporting
confidence: 79%
“…24 Studies have indicated that various insoluble dietary fibers can be fermented by specific intestinal bacteria, or they enhance the SCFA-producing bacteria to promote the production of SCFAs, which is contributed to its anti-obesity effect. 28 In line with those reports, the administration of CL-IDFs or CL-TDFs significantly enriched the family of Lachnospiraceae and could promote SCFA production, suggesting that the anti-obesity effect was correlated with the production of SCFAs. The SCFA concentration suggests that the anti-obesity effect was correlated with the production of SCFAs.…”
Section: Effect Of the Cl-idf And Cl-tdf On Gut Microbiota And Scfas ...supporting
confidence: 79%
“…Alternatively, exogenous short chain fatty acid supplementation is used to restore VFA levels [109]. Metanalytic data show that short chain fatty acid supplementation can significantly reduce plasma levels of high-sensitivity C-reactive protein, LPS, and TNFα in humans and animals [110]. The anti-inflammatory activity of VFA can be synergized by the anti-inflammatory activity exerted by Se itself.…”
Section: Mechanism Of Action Of Se In Ruminal Fermentationmentioning
confidence: 99%
“…The main components of EHR are maltodextrin, oligosaccharide malt and polyglucose. Maltodextrin [ 35 ] is a kind of polysaccharide that is easily absorbable and relieves stress of digestive system for patients; oligosaccharide is characterized by low sweetness, low caloric, hypoosmolality, occurs continuous hydrolysis reaction in intestines which could increases blood glucose slightly and prolong the duration of energy supply; although polyglucose barely provide energy, as soluble cellulose, it increases the intestinal chyme volume and patients’ satiety, slows the absorption of carbohydrate, what is more, the short chain fatty acids produced from polyglucose by intestinal flora enhances intestinal mucosal barrier, reduce the absorption of endotoxin and play an important anti-inflammatory role which maybe one of the factors to relieve IR and promote intestinal peristalsis [ 36 , 37 ]. As a result, in the study oral EHR solution decreased VAS scores of fatigue, hunger and anxiety, reduced the incidence of nausea, enhanced handgrip strength and shorten exhaust time.…”
Section: Discussionmentioning
confidence: 99%